2020
DOI: 10.1038/s42003-020-01227-2
|View full text |Cite|
|
Sign up to set email alerts
|

Nrf2 contributes to the weight gain of mice during space travel

Abstract: Space flight produces an extreme environment with unique stressors, but little is known about how our body responds to these stresses. While there are many intractable limitations for in-flight space research, some can be overcome by utilizing gene knockout-disease model mice. Here, we report how deletion of Nrf2, a master regulator of stress defense pathways, affects the health of mice transported for a stay in the International Space Station (ISS). After 31 days in the ISS, all flight mice returned safely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(72 citation statements)
references
References 44 publications
2
70
0
Order By: Relevance
“…The body weight of adult Nrf2 KO mice was lower compared to WT mice fed a normal diet [ 37 ]. Nrf2 was involved in weight gain in male mice during space travel by maintaining homeostasis of white adipose tissue [ 38 ]. Decreased expression of peroxisome proliferator-activated receptor γ due to Nrf2 deficiency prevented weight gain and obesity from a high fat diet and environmental stress caused by space travel [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The body weight of adult Nrf2 KO mice was lower compared to WT mice fed a normal diet [ 37 ]. Nrf2 was involved in weight gain in male mice during space travel by maintaining homeostasis of white adipose tissue [ 38 ]. Decreased expression of peroxisome proliferator-activated receptor γ due to Nrf2 deficiency prevented weight gain and obesity from a high fat diet and environmental stress caused by space travel [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 was involved in weight gain in male mice during space travel by maintaining homeostasis of white adipose tissue [ 38 ]. Decreased expression of peroxisome proliferator-activated receptor γ due to Nrf2 deficiency prevented weight gain and obesity from a high fat diet and environmental stress caused by space travel [ 37 , 38 ]. In our previous study, the body weight of male control mice was not affected by Nrf2 KO at week 16 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor, erythroid 2-like transcription factor 2 (Nrf2) and its cytoplasmic inhibitor, kelch-like ECH-associated protein 1 (Keap1), comprise a redox-responsive endogenous antioxidant defense module that orchestrates the expression of cytoprotective genes to maintain homeostasis [ 1 ]. Currently in its third decade, Keap1/Nrf2-related research continues to achieve landmarks, such as the recent demonstration of the role of Nrf2 in weight gain during space travel [ 2 ]. While much is already known about the regulation and functioning of the Keap1/Nrf2 pathway, basic research continues to reveal new insights; examples from the present Special Issue include distinct and overlapping roles in gene expression regulation with related cap’n’collar transcription factors Nrf1 and Nrf3 [ 3 ], as well as the connection of Nrf2 to cellular organelles with important emerging roles such as primary cilia [ 4 ].…”
mentioning
confidence: 99%
“…A protective role for Nrf2 in the aging process is further supported by low Nrf2 expression in children with extreme premature vascular ageing due to Hutchinson-Gilford Progeria syndrome (108). Additionally, a recent study conducted in Nrf2 k/o mice sent into space, has revealed that Nrf2-deficiency induces ageing-like changes in plasma metabolites and weight gain (109). While important lessons on protective mechanisms in ageing can be learned from long-lived fish with negligible senescence, such as the Greenland shark (>400 years) and Bowhead whale (>200 years), short-lived fish, such as killifish (13 weeks) have emerged as an important natural animal models for ageing research (105).…”
Section: Negligible Senescence and Environmental Stresswhat Is The Romentioning
confidence: 97%